Nanoscale guiding for cold atoms based on surface plasmons along the tips of metallic wedges - 王正岭 唐伟民 周明 高传玉 (Chinese physics B, 2013)
We propose a novel scheme to guide neutral cold atoms in a nanoscale region based on surface plasmons （SPs） of one pair and two pairs of tips of metallic wedges with locally enhanced light intensity and sub-optical wavelength resolution. We analyze the near-field intensity distribution of the tip of the metallic wedge by the FDTD method, and study the total intensity as well as the total potential of optical potentials and van der Waals potentials for 87 Rb atoms in the light field of one pair and two pairs of tips of metallic wedges. It shows that the total potentials of one pair and two pairs of tips of metallic wedges can generate a gravito-optical trap and a dark closed trap for nanoscale guiding of neutral cold atoms. Guided atoms can be cooled with efficient intensity-gradient Sisyphus cooling by blue-detuned light field. This provides an important step towards the generation of hybrid systems consisting of isolated atoms and solid devices.